Land-use change and landscape fragmentation in central Veracruz, Mexico (1989–2015) - Hernández-Pérez, Ezequiel; García-Franco, José Guadalupe; Vázquez, Gabriela; Cantellano de Rosas, Eliseo (Instituto de Ecología, A.C., 2022)
Deforestation and fragmentation are considered threats to biodiversity. Both processes have negative effects on the function and dynamics of ecological systems at different spatial and temporal scales. Land-use change and landscape fragmentation in the central region of Veracruz, Mexico, were analyzed for the years 1989, 2003, and 2015. Cover classes were obtained from Landsat images, using supervised classification. Vegetation change and loss were quantified, and fragmentation was evaluated using landscape metrics. From 1989 to 2015, the vegetation area decreased 57%, with an annual rate of land cover change of-2.15%. Between 1989 and 2015, there was a decrease in mean fragment size, total core area, contrast index, and mean proximity. The number of fragments, the fragment density, and the total edge length decreased from 1989 to 2003 and subsequently increased in 2015. The study area shows a tendency towards landscape homogenization, where agricultural fragments and secondary vegetation occupy increasingly large areas. Recognizing the vegetation fragments most at risk to land use change is key to assessing their effect on the conservation of biodiversity and the environmental services they provide; it would also make it possible to define conservation policies that help promote sustainable agricultural and livestock practices in this region of Mexico.